Shepherd and Lamb - Kríza, Ildikó (Traditiones (Ljubljana), 1999)
The paper compares the Romanian ballad ˝Miorioa˝ (Lamb) with its Hungarian variant about a murdered mountain shepherd. While the first part of the paper deals with the theoretical aspect of the ballad research its second part focuses on the Hungarian variant of this Romanian ballad which had doubtlesslybecame incorporated into the Hungarian folk tradition by way of Moldavia.
Keywords: Ethnopoetics; ljudske pesmi; slovstvena folklora; balade